Validity of Land Rental Agreement for Foreign Nationals' Borrowing Practices - Rosalia, Raudah (Alauddin Law Development Journal (ALDEV), 2025)
Nominee practice in Indonesia is found in the case of Denpasar High Court Decision, which leases between Indonesian Citizens (WNI) and Foreign Citizens (WNA) are permitted in practice based on Article 45 Letter B of the Basic Agrarian Law. The research method used is normative juridical. The results show that nominee practice includes the preparation of lease agreements that are not related to each other, which shows the characteristics indirectly aims to transfer Ownership Rights to land to foreigners. The legal status and certainty of the Lease Agreement deed along with other supporting agreements made before the Notary can be categorized as legal smuggling, so it is appropriate that the Notary's deeds are declared null and void and have no binding legal force. The land with a Freehold Certificate Number 6196/Canggu which is the object of the case should fall to the State and become State land.